Pochonia chlamydosporia synergistically supports systemic plant defense response in Phacelia tanacetifolia against Meloidogyne hapla - Könker, Jana; Zenker, Sanja; Meierhenrich, Anja; Patel, Anant; Dietz, Karl-Josef (Frontiers in Plant Science, 2025)
The network of antagonistic, neutral, and synergistic interactions between (micro)organisms has moved into the focus of current research, since in agriculture, this knowledge can help to develop efficient biocontrol strategies. Applying the nematophagous fungus Pochonia chlamydosporia as biocontrol agent to manage the root-knot nematode Meloidogyne hapla is a highly promising strategy. To gain new insight into the systemic response of plants to a plant-parasitic nematode and a nematophagous fungus, Phacelia was inoculated with M. hapla and/or P. chlamydosporia and subjected to transcriptome and metabolome analysis of leaves. While the metabolome proved quite stable except for the early time point of 48 h, comparison of the single P. chlamydosporia with the combined treatment revealed even larger effects after 6 d compared to 48 h, aligning with the later root infestation by P. chlamydosporia compared to M. hapla. Simultaneous exposure to both microorganisms showed a stronger overlap with the single M. hapla treatment than P. chlamydosporia. Changes of transcripts and metabolites were higher in the combined treatment compared to the individual inoculations. The results support the conclusion that P. chlamydosporia induces plant defense in a distinct and beneficial manner if combined with M. hapla although plant defense is partly suppressed by the endophytic growth. The results tentatively suggested that the application of P. chlamydosporia as a biocontrol agent against M. hapla can be more effective by supporting these tritrophic interactions with specific additives, such as phytohormones or amino acids in the formulation.